ENGLISH STUDENTS’ PROBLEMS IN PRONOUNCING UNEXIST ENGLISH VOWELS AND CONSONANTS IN INDONESIAN LANGUAGE - Nona Leviakandella (Teaching English and Language Learning English Journal, 2022)
The purpose of this study was to know students' problems in pronouncing unexist English vowels and consonants in Indonesian language. This research was designed as descriptive qualitative method. The subjects of this research were the fourth semester of English Education study Program of Muhammadiyah University of Bengkulu. The instrument of the research were dictionary and online dictionary. The results of the study were: first, in vowels In Indonesian language usually one sound has only one phoneme while in English several rather similar sounds have their own phonemes Second, in consonant. Unexist Manner of articulation for fricative sounds (/v/, /θ/, /ð/, /ʒ/) and unexist place of articulation for labiodental /v/, dental /θ/ (unvoiced) /ð/ (voiced), palate alveolar /ʒ/ in Indonesian language. Keyboard : Pronunciation, Problems, Unexist, English Vowels, English Consonants.